Plant diversity in hedgerows and road verges across Europe. Issue 7 (13th April 2020) - Vanneste, Thomas; Govaert, Sanne; De Kesel, Willem; Van Den Berge, Sanne; Vangansbeke, Pieter; Meeussen, Camille; Brunet, Jörg; Cousins, Sara A. O.; Decocq, Guillaume; Diekmann, Martin; Graae, Bente J.; Hedwall, Per‐Ola; et al.
Abstract: Linear landscape elements such as hedgerows and road verges have the potential to mitigate the adverse effects of habitat fragmentation and climate change on species, for instance, by serving as a refuge habitat or by improving functional connectivity across the landscape. However, so far this hypothesis has not been evaluated at large spatial scales, preventing us from making generalized conclusions about their efficacy and implementation in conservation policies. Here, we assessed plant diversity patterns in 336 vegetation plots distributed along hedgerows and road verges, spanning a macro‐environmental gradient across temperate Europe. We compared herb‐layer species richness and composition in these linear elements with the respective seed‐source (core) habitats, that is, semi‐natural forests and grasslands. Next, we assessed how these differences related to several environmental drivers acting either locally, at the landscape level or along the studied macro‐ecological gradient. Across all regions, about 55% of the plant species were shared between forests and hedgerows, and 52% between grasslands and road verges. Habitat‐specialist richness was 11% lower in the linear habitats than in the core habitats, while generalist richness was 14% higher. The difference in floristic composition between both habitat types was mainly due to species turnover, and not nestedness. Most notably, forest‐specialist richness in hedgerows responded positively to tree cover, tree height and the proportion of forests in the surrounding landscape, while generalist richness was negatively affected by tree height and buffering effect of trees on subcanopy temperatures. Grassland and road verge diversity was mainly influenced by soil properties, with positive effects of basic cation levels on the number of specialists and those of bioavailable soil phosphorus on generalist diversity. Synthesis and applications . We demonstrate that linear landscape elements provide a potential habitat for plant species across Europe, including slow‐colonizing specialists. Additionally, our results stress the possibility for land managers to modify local habitat features (e.g. canopy structure, subcanopy microclimate, soil properties, mowing regime) through management practices to enhance the colonization success of specialists in these linear habitats. These findings underpin the management needed to better conserving the biodiversity of agricultural landscapes across broad geographical scales. Abstract : We demonstrate that linear landscape elements provide a potential habitat for plant species across Europe, including slow‐colonizing specialists. Additionally, our results stress the possibility for land managers to modify local habitat features (e.g. canopy structure, subcanopy microclimate, soil properties, mowing regime) through management practices to enhance the colonization success of specialists in these linear habitats. These findings underpin the management needed to better conserving the biodiversity of agricultural landscapes across broad geographical scales.